THE EFFECT OF SERVICE QUALITY AND NURSE THERAPY COMMUNICATION ON COMPLAINTS HANDLING TOWARDS PATIENT LOYALTY WITH INTERVENING BY PATIENT FAMILY SATISFACTION - Tintin Supriatin; Eka Desy Purnama; Wani Devita Gunardi (ID Solutions, 2022)
Hospital services are an industry based on practical economic principles, efficiency, effectiveness, indicators of patient service quality lie in five dimensions, namely Reliability, Tangibles, Responsivness, Assurance and Empathy. The behavior of using health services in hospitals solely concerns users of the same hospital health services repeatedly. The purpose of this study was to see the direct and indirect relationship between service quality and therapeutic communication in handling complaints against patient loyalty with patient family satisfaction as an intervening variable. This study uses quantitative methods, data analysis using path analysis, Smart PLS software, and the bootsrapping method (random doubling). The technique used is non-probability sampling with a purposive sampling approach. The results showed that (55%) nurses used therapeutic communication well, and (45%) less well. From the results of the hypothesis test, the t-statistical value of 2.265> 1.98 with a p-value of 0.024 <0.05 showed that the effect of nurse therapeutic communication on handling complaints on patient family satisfaction was significant. and the t-statistic value was 2.653 > 1.98 with a p-value of 0.008 < 0.05, indicating that the effect of nurse therapeutic communication on handling complaints on patient loyalty was significant. and the t-statistic value of 2.347 > 1.98 with a p-value of 0.019 <0.05, indicating that the indirect effect of nurse therapeutic communication on handling complaints on patient loyalty through patient family satisfaction is significant.